Integrated mosquito control in Matatang village, Northern Zhejiang, China: an effectiveness assessment - Guo, Song; Huang, Jian; Liu, Ying; Zhang, Rong; Ren, Jiangping; Shi, Xuguang; Sun, Jimin (Frontiers in Public Health, 2025)
Mosquito nuisance and disease transmission have become significant challenges in rural development and tourism. From 2018 to 2021, Matatang village in Jiaxing City, Zhejiang Province, implemented an integrated mosquito control program centered on environmental management and health education. This study evaluated the effectiveness of mosquito control in Matatang village by assessing mosquito abundance, villagers’ knowledge, behaviors, perceptions regarding mosquito control, and satisfaction rates. Mosquito abundance data were collected during the intervention phase (2018) and maintenance phase (2021), including adult and larval mosquito surveillance. Villagers’ knowledge, behaviors, perceptions, and satisfaction were assessed through surveys during the maintenance phase (2021). A significant decline in abundance was observed in all mosquito species between monitoring periods. Surveillance results showed that the mean adult mosquito index in Matatang village was 9.35 ± 9.82 in 2018 and 1.95 ± 1.49 in 2021, compared to 6.45 ± 4.46 in the control village in 2021. The mean larval mosquito index in Matatang village was 36.00 ± 39.19 in 2018 and 9.50 ± 4.11 in 2021, whereas the control village had a mean larval index of 35.50 ± 27.25 in 2021. Statistical analysis revealed significant differences in monthly adult and larval mosquito indices between Matatang village and the control village in 2021 (p < 0.05). Survey results indicated significantly higher knowledge levels of basic mosquito-related information among Matatang village residents compared to the control village. Notably, awareness of mosquito breeding sites exceeded 80% in Matatang village, while remaining below 25% in the control village, with this difference demonstrating statistical significance (p < 0.001). Behavioral practices such as eliminating stagnant water, cleaning ditches, and regularly changing water for hydroponic plants were also significantly more prevalent in Matatang village. Moreover, 73.33% of Matatang villagers expressed satisfaction with local mosquito control efforts, compared to only 10.00% in the control village (χ2 = 24.754, p < 0.001). This study demonstrates that an integrated mosquito control model emphasizing environmental management and health education can foster long-term self-management and proactive maintenance among villagers. Such an approach not only sustainably reduces mosquito abundance but also improves rural living conditions, highlighting its critical public health significance.